Dengue fever in Morocco: result of surveillance during the year 2017 and first imported cases - Bajjou, Tahar; Akhouad, Youssef; Hilali, Farida; Elkochri, Safae; Laraqui, Abdelilah; Touil, Nadia; Lahlou Amine, Idriss; Mahassine, Fattouma; Sekhsokh, Yassine (International Journal of Research in Medical Sciences, 2018)
Dengue is a significant mosquito-borne infection in humans, and its worldwide prevalence is rapidly increasing. The vector aedes albopictus has been revealed recently in the town of Rabat. Morocco established a program of active surveillance of dengue fever comprising many hospitals and laboratories across the kingdom. The purpose of this work is to describe the result of the surveillance of the dengue virus (DENV) infection during the year of 2017 among Moroccans and tourists who presented in our hospital with clinical signs of infection and to report the first confirmed positive cases of Dengue. From 20 December 2016 to 20 December 2017, 21 patients were hospitalized for suspicion of DENV infection. Half of them were returning from Côte d’Ivoire which is a popular tourist and business country for Moroccans and where an outbreak of DENV was confirmed on July 2017. Fever, headache, arthralgia-myalgia and malaise in addition to the notion of return from an endemic country justify in clinicians the demand for analysis of detection of dengue virus by RT-PCR. Dengue infection was confirmed in two patient both coming from Côte d’Ivoire, a Moroccan and an Ivorian who were staying in Abidjan during the period of the outbreak of 2017.